Building Resilience Along the Indonesia–Timor Leste Border: The Role of Local Resources in Strengthening the Rural Economy - Herry Aprilia Manubulu; Anggreini D. N. Rupidara; Yunialdi H. Teffu (Indonesian Journal of Enterprise Architecture, 2026)
Border villages in Indonesia–Timor Leste face persistent economic challenges despite abundant natural resources. Unlike previous studies that primarily focus on general rural development or quantitative assessments of village fund effectiveness, this study fills the gap by qualitatively examining the role of local resource management in strengthening economic resilience specifically in the under-researched border region of East Kobalima District, Malaka Regency. Using a qualitative case study design, data were collected through in-depth interviews, direct observation, and secondary administrative data from four villages: Alas, Alas Selatan, Alas Utara, and Kotabiru. Key findings reveal that although forest and agricultural resources (e.g., teak, candlenut, maize, and medicinal plants) are abundant, 75% of households earn less than IDR 7.5 million per year, and low education levels (20% never attended school; 19% incomplete primary) constrain optimal resource utilization. Community participation remains limited to implementation stages, with minimal involvement in planning and evaluation. Market access is restricted to weekly traditional markets, limiting income generation. The novelty lies in explicitly identifying that weak synergy between natural, human, and social resources rather than resource scarcity is the primary barrier to economic resilience. This study concludes that participatory governance, human resource capacity building, and strengthening village economic institutions are critical. Implications for policy include integrated cross-border market strategies and university-community partnerships to transform local resources into high-value economic assets.